Hospital Governance and Appropriation of User Services by Medical and Social Staff: The Case of the Douala-Cameroon Hospitals (Global Journal of Management and Business Research, 2022)
The transposition of the corporate governance mode to hospital governance for several decades J Vallejo 2018 has led to the study of possible causal links between governance systems aimed at regulating the behaviour of medical staff and the improvement of services to users of these hospital structures Analysing this issue within the Douala Hospital Centres this article raises the following question How and in what way does hospital governance impact on the appropriation of user services by medical and social staff in the Douala Hospital Centres This led us to mobilise a qualitative-quantitative methodology which enabled us to collect and analyse data from 250 people administration medical staff users etc using online data collection tools stat-survey The numerical and qualitative data collected were analysed using SPSS software and interpreted in the light of the agency s theories
Keywords: hospital governance - ownership of user services - medical and social staff - patients - douala hospital – Cameroon